14.8k views
3 votes
( -7v 4 - 5v ) - ( -5v 3 - 2v ) + ( -7v - 6v 4 - 4v 3 ) simplified

1 Answer

4 votes

Answer:

-13v^4 + v^3 - 10v (if simplified)

Explanation:

combine like terms

(-7v^4 - 5v) - (-5v^3 - 2v)+ ( - 7v - 6v^4 - 4v^3)

-7v^4 + -6v^4 = -13v^4

-5v^3 + -4v^3 = v^3 (the five becomes positive because of the negative sign infront of the parenthesis) Example: -(-5v^3) = +5v^3

-13v^4 + v^3 -5v -(-2v) -7v (now we have the -2 left alone in the parenthesis which means it becomes positive too) Example: -(-2v) = +2v

-5v +2v - 7v = -3v -7v = -10v

Answer: -13v^4 + v^3 - 10v

User Jiyoung
by
5.9k points